ENGAGEMENT RESOURCES IN ONLINE OPINION ARTICLES: AN APPRAISAL ANALYSIS OF EDUCATIONWEEK - Auliya Hasanah; Marwito Wihadi; Yayan Suryana (Universitas Lambung Mangkurat, 2025)
This study aims to determine the sub-categories of engagement and their functions in opinion articles from the “EducationWeek” homepage. The theory used by the researcher comes from Martin & White regarding the engagement of appraisal theory. A qualitative method was used with a discourse analysis approach and document analysis as the instrument of this study. The result shows that 185 clauses containing engagement subcategories (Monogloss, Deny, Counter, Concur, Pronounce, Endorse, Entertain, Acknowledge, Distance) were found in the three opinion articles. The functions of the subcategories of engagement used by the authors in the three opinion articles include monogloss to express a single viewpoint, deny to reject other views, counter to present two different statements, concur to express the author's support, pronounce to emphasize the author's statement, endorse to present a valid source, entertain to allow space, acknowledge to present other voices implicitly, and distance to provide quotes that seem to scare. This study is expected to increase the knowledge of readers and a reference for further researchers on different topics or media of articles, various backgrounds of writers of articles, other genres such as news, advertisement, editorials, etc., or select certain sub-categories of engagement, like acknowledge or endorse